IMPLEMENTATION OF THE HIGH TOUCH, HIGH TEACH, AND HIGH TECH FRAMEWORK FOR BEGINNER BATIK BUSINESS - Ratnawati, Ike; Rahman Prasetyo, Abdul; Iriaji, Iriaji; Aruna, Alby; Marcelliantika, Adinda; Putri Surya, Eka; Atma Wijaya, Ginanjar (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
The batik industry in Indonesia faces the challenge of modernization while maintaining its rich traditions. Batik beginners are often hampered by limited knowledge and access to technology. This research aims to explore the effectiveness of the High Touch, High Teach, and High Tech framework in supporting start-up batik businesses for innovation and sustainable growth. This research uses the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation) to implement the framework. The Analysis Phase involves collecting data about the needs of a budding batik business. The Design and Development stage builds a strategy that integrates High Touch, High Teach, and High Tech approaches. Implementation was carried out through pilots in a number of start-up batik businesses, with assistance and training. Evaluation involves validation by batik experts and analysis of feedback from batik entrepreneurs. This framework shows significant improvements in product quality, process efficiency, and market reach of start-up batik businesses. Validation by batik experts confirms an increase in the combination of traditional values and modern innovation.